Histopathological Changes of Erythrocyte and Quantity of immature Erythrocytes in Tegal Duckling (Anas Javanica) Induced by Lead (Pb) - Hamdani Budiman; Dwinna Aliza (Jurnal Kedokteran Hewan, 2010)
The aim of this research is to find out the histopathological changes of erythrocyte and the quantity of immature erythrocyte of tegal duckling treated with lead (Pb). Twenty five young female ducks with the age of 7 days and 60.55.07 g body weight alloted into 4 treatment groups and 1 control group (Ko) with 5 replication each. The treatment group fed with K1 (5.7), K2 (11.4), K3 (17.1), and K4 (22.8) mg Pb/kg body weight for 10 days, respectively. Young ducks showed clinical symptoms such as the color of feces were brown to black, green color of diarrhea, anemic and decreasing body weight. Histopathologically, erythrocyte showed that immature and abnormal in shape (like teardrops, dumb bell, and bottles). The result of variant analysis followed by linier regression shows that the higher the dosage of Pb in diet the higher the quantity of immature erythrocyte andabnormal erythrocyte shape found (P0.01).